Flexible mechanisms of Kyoto protocol: An examination on Australia and Malaysia position / Abdullah Johari Hamzah - Abdullah Johari, Hamzah (2009)
Flexible mechanism are marked-based approach to achieve the objective of the United Nation framework convetion on climate change.